2023
DOI: 10.1002/tox.24097
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol alleviates imidacloprid‐induced mitochondrial apoptosis, necroptosis, and immune dysfunction in chicken lymphocyte lines by inhibiting the ROS/MAPK signaling pathway

Xiaodan Wang,
Jiatong Sun,
Tong Xu
et al.

Abstract: Imidacloprid (IMI) is a neonicotinoid insecticide with the highest global market share, and IMI exposure in the environment can negatively affect many nontarget organisms (a general term for organisms affected by drugs other than target organisms). Resveratrol (RSV), a non‐flavonoid polyphenolic organic compound derived from peanuts, grapes, and other plants, has anti‐inflammatory and antioxidant effects. It is currently unclear how RSV protects against cell damage caused by IMI. Therefore, we established an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 73 publications
0
1
0
Order By: Relevance
“…This highly reactive oxygen containing species induces mitochondrial dysfunction and stimulates various signaling proteins kinases. These oxidative damage conditions can initiate autophagosome formation inducing autophagy [ 44 , 45 ]. In biological system, NPs tends to form protein-NP corona depending on protein affinity and NPs characteristics.…”
Section: Inhalation Exposure Modified Mtor Signaling Contributing To ...mentioning
confidence: 99%
“…This highly reactive oxygen containing species induces mitochondrial dysfunction and stimulates various signaling proteins kinases. These oxidative damage conditions can initiate autophagosome formation inducing autophagy [ 44 , 45 ]. In biological system, NPs tends to form protein-NP corona depending on protein affinity and NPs characteristics.…”
Section: Inhalation Exposure Modified Mtor Signaling Contributing To ...mentioning
confidence: 99%
“…Wang et al. ( 2024 ) reported that the imidacloprid insecticide triggers mitochondrial apoptosis (Caspase‐3, Caspase‐9, Bax and Cyt‐c), necroptosis (Caspase‐8, RIPK1, RIPK3 and MLKL) and immune dysfunction in chickens by activating the key components of the mitogen‐activated protein kinase signalling pathway, resulting in oxidative stress. They also observed that these dysfunctions are significantly reduced by the polyphenolic compound Resveratrol.…”
Section: Introductionmentioning
confidence: 99%